Current trends in River Bathymetry using UAV-borne technology to inform E-flow assessments in Southern Africa - Singh, K. (International Water Management Institute, 2023)
Freshwater, constituting a mere 2.5% of Earth's total water, is a critical resource facing escalating competition due to an anticipated global population surge to 9.7 billion by 2050. Southern Africa is characterized by uneven water distribution and quality challenges which exacerbates these issues. Environmental flow (E-flow) management is a crucial approach that quantifies water requirements for maintaining ecological integrity, aiming to balance human and environmental water needs. Including Eflows in management helps to ensure sustainability of water resources River bathymetry is a core part of E-flow assessments. This document reports on core research within a project that delves into management of E-flows in the Limpopo and neighbouring basins in Southern Africa. It covers a scientific investigation to determine optimal water quantities and qualities for river systems and to assist with their management. The report focuses particularly on the use of bathymetric surveys, specifically the need for high-resolution Digital Elevation Models (DEMs) to inform hydraulic modelling. The spatial and temporal variability of bathymetry is crucial for applications ranging from flood risk mitigation to ecosystem studies and for long-term management of E-flow implementation. While traditional Total Station Theodolite (TST) surveys provide accurate ground control points and in the past were the basis for river hydraulic studies, they are limited in scale and efficiency. In situ measurements, despite their accuracy, may lack spatial representativeness and are resource intensive. Remote sensing techniques, particularly Unmanned Aerial Vehicles (UAVs), offer an alternative for bathymetric data collection driven by their ability to access challenging areas of a river and provide high-resolution data at relatively low cost. To this end, this report focuses on direct methods for bathymetric data collection, exploring optical and acoustic approaches. The primary objective was to explore and investigate UAV-based waterpenetrating surveying techniques to create high-resolution DEMs for hydraulic modelling linked to Eflow studies. A review of recent, relevant literature indicated that airborne laser bathymetry appeared preferential in the context of E-flows, compared to spectrally derived bathymetry, multimedia photogrammetry, Ground-Penetrating Radar (GPR), and Sound Navigation and Ranging (SONAR) techniques. Currently, the RIEGL VQ-840-GL green lidar sensor appears to be the forefront technology for use in E-flows UAV-borne bathymetric surveys. This research aims to contribute valuable insights into efficient and cost-effective methods for E-flow studies, addressing the growing challenges in water resource management.